Incidence of Clostridioides difficile infection (CDI) related to antibiotic prescribing by GP surgeries in Wales. (21st June 2021) - Tydeman, Florence; Craine, Noel; Kavanagh, Kimberley; Adams, Helen; Reynolds, Rosy; McClure, Victoria; Hughes, Harriet; Hickman, Matt; Robertson, Chris
Abstract: Background: Clostridioides difficile infection (CDI) is a healthcare-acquired infection (HAI) causing significant morbidity and mortality. Welsh CDI rates are high in comparison with those in England and Scotland. Objectives: This retrospective ecological study used aggregated disease surveillance data to understand the impact of total and high-risk Welsh GP antibiotic prescribing on total and stratified inpatient/non-inpatient CDI incidence. Methods: All cases of confirmed CDI, during the financial years 2014–15 to 2017–18, were linked to aggregated rates of antibiotic prescribing in their GP surgery and classified as 'inpatient', 'non-inpatient' or 'unknown' by Public Health Wales. Multivariable negative-binomial regression models, comparing CDI incidence with antibiotic prescribing rates, were adjusted for potential confounders: location; age; social deprivation; comorbidities (estimated from prevalence of key health indicators) and proton pump inhibitor (PPI) prescription rates. Results: There were 4613 confirmed CDI cases, with an incidence (95% CI) of 1.44 (1.40–1.48) per 1000 registered patients. Unadjusted analysis showed that an increased risk of total CDI incidence was associated with higher total antibiotic prescribing [relative risk (RR) (95% CI) = 1.338 (1.170–1.529) per 1000 items per 1000 specific therapeutic group age-sex related GP prescribing units (STAR-PU)] and that high-risk antibiotic classes were positively associated with total CDI incidence. Location, age ≥65 years and diabetes were associated with increased risk of CDI. After adjusting for confounders, prescribing of clindamycin showed a positive association with total CDI incidence [RR (95% CI) = 1.079 (1.001–1.162) log items per 1000 registered patients]. Conclusions: An increased risk of CDI is demonstrated at a primary care practice population level, reflecting their antibiotic prescribing rates, particularly clindamycin, and population demographics.